2015
DOI: 10.1097/hp.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 238U and 232Th in Petrol, Gas-oil and Lubricant Samples by Using Nuclear Track Detectors and Resulting Radiation Doses to the Skin of Mechanic Workers

Abstract: Workers in repair shops of vehicles (cars, buses, truck, etc.) clean carburetors, check fuel distribution, and perform oil changes and greasing. To explore the exposure pathway of (238)U and (232)Th and its decay products to the skin of mechanic workers, these radionuclides were measured inside petrol, gas-oil, and lubricant material samples by means of CR-39 and LR-115 type II solid state nuclear track detectors (SSNTDs), and corresponding annual committed equivalent doses to skin were determined. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Equivalent doses (Sv) received by eye tissues of patients wearing contact lenses resulting from the transfer of all residual energies of an alpha-particle of index j and initial energy E αj , emitted by a radionuclide of the 238 U series and an alpha-particle of index j′ and initial energy E αj ′ emitted by a radionuclide of the 232 Th series are respectively expressed by the following relationships (Misdaq et al 2015):…”
Section: Methods Of Studymentioning
confidence: 99%
“…Equivalent doses (Sv) received by eye tissues of patients wearing contact lenses resulting from the transfer of all residual energies of an alpha-particle of index j and initial energy E αj , emitted by a radionuclide of the 238 U series and an alpha-particle of index j′ and initial energy E αj ′ emitted by a radionuclide of the 232 Th series are respectively expressed by the following relationships (Misdaq et al 2015):…”
Section: Methods Of Studymentioning
confidence: 99%
“…The radionuclides of the 238 U, 232 Th, and 235 U series emit alpha and beta-particles as well as gamma rays. It has been shown that alpha radiation doses are deposited in skin of individuals following the immersion in thermal water [1], and application of olive oil [2], medical drugs [3] and petrol *Corresponding author's E-mail ID: misdaq@uca.ac.ma [4]. It also has been shown that alpha doses are deposited in the eye tissues of individuals from the plate out of radon and thoron progeny present in ambient air in dwellings and workplaces [5].…”
Section: Introductionmentioning
confidence: 99%
“…The annual effective doses initiated of 238 U, 232 Th were evaluated in different foods using the International Commission on Radiological Protection (ICRP) using the dose coefficients by ingestion [4], in the different samples olive oil [5] and in oil and lubricant oil [6]. In this work, we use a method based on the use of nuclear solid trace detectors (SSNDs) to measure the concentrations of 238 U, 232 Th and 222 Rn in the various table oil samples in order to evaluate radiation doses received by consumers following ingestion of these table oils.…”
Section: Introductionmentioning
confidence: 99%